2019
DOI: 10.1016/j.neuron.2019.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Central Processing of Itch in the Midbrain Reward Center

Abstract: Highlights d Itch elicits distinct activation patterns of GABA and DA neurons in VTA d GABA neurons signal aversion toward itch d DA neurons mediate reward to scratch-induced relief of itch d VTA neurons regulate scratching behaviors in chronic itch

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 64 publications
1
47
0
Order By: Relevance
“…Consistent with addiction, the DA pathway from VTA to NAc was activated in a chronic itch animal model . Moreover, chronic itch patients reported intense pleasurable sensation, and evoked activations in the reward‐related areas induced by scratching were significantly increased .…”
Section: Clinical and Neurobiological Similarities Between Addiction mentioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with addiction, the DA pathway from VTA to NAc was activated in a chronic itch animal model . Moreover, chronic itch patients reported intense pleasurable sensation, and evoked activations in the reward‐related areas induced by scratching were significantly increased .…”
Section: Clinical and Neurobiological Similarities Between Addiction mentioning
confidence: 87%
“…Change in VTA activity also correlated significantly with scratching‐induced pleasure in humans . Furthermore, a recent animal study demonstrated that the system whereby VTA DA neurons mediate reward from itch relief concorded with that in humans with involvement of the midbrain reward centre in scratching‐induced pleasantness . The urge for a pleasant sensation induced by scratching an itch can be considered similar to the positive reinforcement involved in satisfying a crave for drugs in the initial stages of drug addiction.…”
Section: Clinical and Neurobiological Similarities Between Addiction mentioning
confidence: 99%
“…The injection method and dose of the virus referred to our previous studies (Su et al, 2019). Briefly, rats were first subjected to anesthesia (3% pentobarbital sodium, 40 mg/kg, i.p.)…”
Section: Virus Injectionmentioning
confidence: 99%
“…The optical fiber implantation methods and laser light stimulation parameters referred to our previous studies and other related articles (Su et al, 2019). The specific steps were as follows: optical fibers were implanted at about 4 weeks after virus injection, rats were anesthetized with 3% pentobarbital sodium (40 mg/kg, i.p.)…”
Section: Optical Fiber Implantation and Blue Laser Light Stimulationmentioning
confidence: 99%
“…Our brains actually reward us for scratching. That sense of euphoria originates from dopaminergic neurons in the ventral tegmental area, the same reward center of the brain that' give rise to the sensation of orgasm and is implicated in drug addiction 59 . So if scratching an itch is detrimental then why do our brains encourage us to do it?…”
Section: Introductionmentioning
confidence: 99%